Obstetric comorbidity index and the odds of general vs. neuraxial anesthesia in women undergoing cesarean delivery: a retrospective cohort study. (August 2022) - Singh, S.; Farber, M.K.; Bateman, B.T.; Lumbreras-Marquez, M.I.; Richey, C.J.; Easter, S.R.; Fields, K.G.; Tsen, L.C.
Highlights: The obstetric comorbidity index (OB-CMI) is a composite measure of comorbidities. OB-CMI predicts maternal morbidity, mortality, and intensive care unit admission. There is a move to decrease general anesthesia (GA) for cesarean delivery. This study found an association between OB-CMI and GA for cesarean delivery. Abstract: Background: Maternal and fetal concerns have prompted a significant reduction in general anesthesia (GA) use for cesarean delivery (CD). The obstetric comorbidity index (OB-CMI) is a validated, dynamic composite score of comorbidities encountered in an obstetric patient. We sought to estimate the association between OB-CMI and odds of GA vs. neuraxial anesthesia (NA) use for CD. Methods: In this single-center, retrospective cohort study conducted at a large academic hospital in the United States of America, OB-CMI was calculated on admission and every 12 h for women undergoing CD at ≥23 weeks' gestation (n=928). The CD urgency, anesthesia type, and most recent OB-CMI were extracted from the medical record. The association between OB-CMI and GA use was estimated by logistic regression, with and without adjustment for CD urgency, parity and race. Results: Each one-point increase in OB-CMI was associated with a 32% (95% confidence interval [CI] 17% to 48%) increase in the odds of GA use (Model 1, area under the receiver operating characteristic curve [AUC] 0.708, 95% CI 0.610 to 0.805). The AUC improved to 0.876 (95% CI 0.815 to 0.937) with the addition of emergent CD (Model 2, P  <0.001 vs. Model 1), but not parity and race (Model 3, AUC 0.880, 95% CI 0.824 to 0.935; P =0.616 vs. Model 2). Conclusions: The OB-CMI is associated with increased odds of GA vs. NA use for CD, particularly when emergent. Collected in real time, the OB-CMI may enable prophylaxis (e.g. comorbidity modification, earlier epidural catheter placement, elective CD) or preparation for GA use.